Thermal Degradation of Face Mask Waste through Pyrolysis at Different Temperatures for Value-Added Products - Nikola Cajova Kantova; Michal Holubcik; Robert Cibula; Katerina Benova; Jachym Muck; Jan Najser (Scientific Data)
Abstract The widespread use of protective face masks to prevent the transmission of viral diseases has led to a significant increase in plastic waste. This study investigates the conversion of disposable face masks into valuable solid, oil, and gas products through pyrolysis. Two types of disposable masks were used as input materials: FFP2 face masks and ordinary face masks. The pyrolysis reactor was heated to various target temperatures (350, 400, 450, 500, and 550 °C). Particular attention was given to a detailed analysis of the physicochemical properties of the raw materials and the characterization of the pyrolysis products at different temperatures. The measured data provide a basis for analyzing the pyrolysis process of face masks and respirators under varying thermal conditions. Identifying the relationships between input materials, the pyrolysis process, and the properties of the resulting products could enable the production of targeted products with high added value.